Periodontal diseases and tooth wear in sheep flocks in the State of Goiás, Brazil - Martins, Andressa S.; Silva, Tamires A.; Athayde, Flávia R.F. [UNESP]; Saraiva, Júlia R. [UNESP]; Mendes, Juliana G.; Cardoso, Maria Vitória S.; Dutra, Iveraldo S. [UNESP]; Borsanelli, Ana Carolina (FapUNIFESP (SciELO), 2023)
Dental and periodontal affections consist of health concerns of great importance in sheep flocks, as they affect the health and welfare of animals and represent one of the main causes of premature slaughter. Studies on the occurrence of these conditions in sheep are scarce in Brazil. The present study aimed to evaluate the prevalence of periodontal diseases and tooth wear in sheep flocks in the State of Goiás. For this, a clinical oral examination was conducted on 325 sheep from seven farms in six municipalities of the State. Periodontal lesions, characterized by gingival recession in at least one incisor tooth, were observed in 48.3% (157/325) of the sheep, while in cheek teeth it occurred in 13.2% (43/325) of the evaluated sheep. Dental wear on cheek teeth was identified in 69.2% (255/325) of the sheep, and 10.7% (35/325) of the ovines showed dental wear on incisor teeth. Sheep older than 36 months had an increase in the frequency of tooth wear. A total of 171 (52.62%) out of the 325 examined sheep had signs of bleeding on probing, which is compatible with gingivitis, and 69 (40.36%) were older than 36 months. Thirty-eight (11.69%) out of the 325 evaluated ovines had gingivitis in all teeth, among which 21 (55.26%) were older than 36 months. Logistic regression analysis allowed the observation that age was associated with the occurrence of gingivitis. Less frequent changes such as periodontal pockets and loss of at least one tooth were also observed in 4.9% (16/325) and 17.8% (58/325) of the sheep, respectively. It indicates that the presence of periodontal diseases and tooth wear is a common occurrence in the evaluated flocks. Therefore, there is a need to include the oral health of sheep in the routine of the farm as an essential preventive measure to improve the quality of life, animal welfare, and zootechnical indices.
Doenças periodontais e desgaste dentário em rebanhos ovinos no Estado de Goiás, Brasil.
Keywords: Brazil; dental diseases; gingivitis; periodontal disease; Periodontitis; sheep; tooth wear